Simultaneous Method Development And Validation Of Vildagliptin And Metformin In Bulk By Rp-Hplc - Saniya, Saniya; Kumar Brahma, Dillip; Chakraborthy, Gunosindhu; Kumar, Jayendra; Suresh, R.; Kumar Jha, Abhimanyu; Gupta, Shivani; Rakhamaji Dhavade, Ashwini (Journal of Neonatal Surgery, 2025)
The research goal is to provide a quick, easy, accurate, and economical RP-HPLC technology for simultaneously analyzing the amounts of Vildagliptin and Metformin in bulk samples and pharmaceutical products. The separation of Vildagliptin (VLD) and Metformin (MTF) has been accomplished successfully with this approach. An Xterra C18 column (250 mmL×4.6 mm) analytical column operating at 210 nm was used to carry out the separation. The mobile phase was made up of a 40:40:20 mixture of phosphate buffer, acetonitrile, and water, with the buffer's pH set to 5.5. At a flow rate of 1.0 ml/min, the separation was performed in isocratic elution mode. Using a linear calibration curve and PDA detection at 210 nm, metformin and vildagliptin were quantitatively analyzed. For accurate quantification, the concentration ranges of 10–50 µg/ml (correlation coefficient of 0.9998) for MTF and 1–5 µg/ml (correlation coefficient of 0.9998) for VLD were employed. Vildagliptin had a limit of detection (LOD) of 0.332 µg/ml, while metformin had a LOD of 1.662 µg/ml. Whether employed alone or in combination, the suggested approach is ideal for use in quality-control labs for pharmaceutical quantitative analysis and bulk analysis. This method is distinguished by its efficiency and simplicity while maintaining a high degree of precision and accuracy